New Wavelet Method For Solving Partial Differential Equations - et. al, Ahmed Mohammed Qasim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper a new wavelet formula is derived based on the definition of the convolution between the Haar and CAS wavelets, while finding the integrals of the proposed formula analytically. An outline of the proposed method is written with the collocation points for solving partial differential equations. From the comparison of the numerical results of the proposed methods with the exact solution to solve three problems, we concluded that the suggested method is more accurate, better, and nearer to an exact solution.